2007
DOI: 10.1007/s11113-007-9033-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family policies on fertility in industrialized countries: a review of the literature

Abstract: This paper examines the theoretical propositions and empirical evidence linking policies and fertility. More specifically, the analysis presented in this paper draws attention to the complex mechanisms that theoretically link policies and demographic outcomes: mechanisms that involve imperfect information and decisions that are rationally bound by very specific circumstances. As to the empirical evidence, studies provide mixed conclusions as to the effect of policies on fertility. While a small positive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
361
2
35

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(412 citation statements)
references
References 64 publications
14
361
2
35
Order By: Relevance
“…Yet several studies have found that, unlike in developing countries, European women who invest more in education do not necessarily intend to have a smaller family size than their less-educated counterparts (e.g., Testa 2014; see also Esping-Andersen 2009;Kravdal and Rindfuss 2008). Indeed, because of their ability to break traditional roles, to achieve more gender equality in the division of household labour, and to attain higher economic assets, highly educated women may have better opportunities to balance work and family (Gauthier 2007), and therefore they may even tend to plan more children than women with low education. Following this line of research, we anticipate that daughter's level of education is positively associated with daughter's number of intended children (H2).…”
Section: Human Capital and Fertility Intentionsmentioning
confidence: 99%
“…Yet several studies have found that, unlike in developing countries, European women who invest more in education do not necessarily intend to have a smaller family size than their less-educated counterparts (e.g., Testa 2014; see also Esping-Andersen 2009;Kravdal and Rindfuss 2008). Indeed, because of their ability to break traditional roles, to achieve more gender equality in the division of household labour, and to attain higher economic assets, highly educated women may have better opportunities to balance work and family (Gauthier 2007), and therefore they may even tend to plan more children than women with low education. Following this line of research, we anticipate that daughter's level of education is positively associated with daughter's number of intended children (H2).…”
Section: Human Capital and Fertility Intentionsmentioning
confidence: 99%
“…Proponents of comparative welfare state research have pointed out that policies in modern societies that help mothers to combine work and family life are also conducive to higher fertility (Bernhardt 1993;Esping-Andersen 1999Gauthier 2007;Matysiak and Vignoli 2013;McDonald 2000;Neyer and Andersson 2008). The male-breadwinner family model, which was dominant for several decades, has increasingly become viewed as a precarious arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Al igual que Suecia, este desempeño se conjuga con la incorporación en la sociedad francesa de los valores y características propios de la Segunda Transición Demográfica 7 . Nuevamente, con todas las prevenciones del caso, distintos autores interpretan que la explicación más probable para la fecundidad relativamente alta de Francia es una exitosa política familiar (FLAQUER, 2000;GAUTHIER, 2007;THÉVENON, 2009).…”
Section: Los Modelos De Política En La Experiencia Europeaunclassified
“…En todo caso, lo sugerido más arriba para el caso de Suecia puede mantenerse en términos generales: los mejores resultados (prevención de la caída hacia niveles "lowestlow", mayor satisfacción con la fecundidad, mejores condiciones de crianza en términos de corresponsabilidad colectiva) se han dado allí donde existen abordajes multidimensionales y sostenidos en el tiempo, generando previsibilidad en las condiciones en las que ejerce la paternidad y maternidad, a través del efecto conjunto de provisión de servicios de cuidados infantiles y ampliación de tiempos y espacios para la crianza durante todas las etapas de la niñez (TAKAYAMA;WERDING, 2009;THÉVENON, 2009;GAUTHIER, 2007).…”
Section: Los Modelos De Política En La Experiencia Europeaunclassified